REGULATION OF METABOLISM IN TRANSGENIC PLANTS - Sonnewald, Uwe; et al. (1995)
This review discusses how genetically manipulated plants are being used to study the regulation of metabolism in plants, using carbohydrate metabolism as an example. The molecular tools required are introduced, including the history of Agrobacterium tumefaciens-mediated gene transfer and other transformation techniques, the availability of promoters to achieve a specific or induced expression, strategies to target proteins to subcellular compartments of the cell, and the use of antisense or cosuppression to inhibit expression of endogenous genes. A discussion then follows of how such plants can be used in biochemical and physiological experiments to identify and quantify the importance of enzymes and processes that control metabolic fluxes, storage, and growth These results are leading to a reassessment of ideas about metabolic regulation and have consequences for design of bioengineering strategies in plants. Emerging commercial applications are also surveyed.
Keywords: TRANSGENIC PLANTS; CARBOHYDRATES; PHOTOSYNTHESIS; SUCROSE; STARCH; BIOENGINEERING